Cognitive screening tools for identification of dementia in illiterate and low-educated older adults, a systematic review and meta-analysis - Paddick, Stella-Maria; Gray, William K.; McGuire, Jackie; Richardson, Jenny; Dotchin, Catherine; Walker, Richard W. (International psychogeriatrics, 2017)
ABSTRACTBackgroundThe majority of older adults with dementia live in low- and middle-income countries (LMICs). Illiteracy and low educational background are common in older LMIC populations, particularly in rural areas, and cognitive screening tools developed for this setting must reflect this. This study aimed to review published validation studies of cognitive screening tools for dementia in low-literacy settings in order to determine the most appropriate tools for use. MethodA systematic search of major databases was conducted according to PRISMA guidelines. Validation studies of brief cognitive screening tests including illiterate participants or those with elementary education were eligible. Studies were quality assessed using the QUADAS-2 tool. Good or fair quality studies were included in a bivariate random-effects meta-analysis and a hierarchical summary receiver operating characteristic (HSROC) curve constructed. ResultsForty-five eligible studies were quality assessed. A significant proportion utilized a case–control design, resulting in spectrum bias. The area under the ROC (AUROC) curve was 0.937 for community/low prevalence studies, 0.881 for clinic based/higher prevalence studies, and 0.869 for illiterate populations. For the Mini-Mental State Examination (MMSE) (and adaptations), the AUROC curve was 0.853. ConclusionNumerous tools for assessment of cognitive impairment in low-literacy settings have been developed, and tools developed for use in high-income countries have also been validated in low-literacy settings. Most tools have been inadequately validated, with only MMSE, cognitive abilities screening instrument (CASI), Eurotest, and Fototest having more than one published good or fair quality study in an illiterate or low-literate setting. At present no screening test can be recommended.